PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM BERBASIS BUDAYA RILIGIUS DI SEKOLAH - Azhar (FITRAH was published by the Center for Research and Community Service (LP2M) Ar-Raniry Islamic State University Banda Aceh, 2022)
The formation of a religious culture in schools can be developed through the development of an Islamic Religious Education (PAI) curriculum. This is done to achieve the goals of national education as stipulated in Law Number 20 of 2003, article 3 concerning the National Education System, the purpose of national education is to develop the potential of students to become human beings who believe and fear God Almighty, have noble character. , healthy, knowledgeable, capable, creative, independent, and become a democratic and responsible citizen. The purpose of this article is to find the cultivation of religious values ​​in the development of the PAI curriculum. This study uses qualitative methods by examining the theories developed by experts, then analyzed and conclusions drawn. The results of the study show that the formation of a religious culture is carried out through conditioning the school atmosphere with religious values ​​that are applied to the behavior and activities of students. This can be developed through exemplary behavior of leaders; creation of a religious atmosphere; implementation of religious ritual activities; and character building.